AB0893 THE EFFECTS OF THREE DIFFERENT VITAMIN D3 SUPPLEMENTATION REGIMENS IN DEFICIENT SUBJECTS - A RANDOMIZED OPEN-LABEL PARALLEL GROUP STUDY. (2nd June 2020) - Fassio, A.; Adami, G.; Viapiana, O.; Orsolini, G.; Giollo, A.; Rossini, M.; Gatti, D.
Abstract : Background: Currently, most experts agree that levels of serum 25OH-Vitamin D (25OHD) lower than 20 ng/mL represent an acceptable threshold for deficiency (1). However, recommendations for vitamin D supplementation vary between scientific societies, and the best regimen to treat deficient patients is still not clear (1). Objectives: The aim of our study was to compare the pharmacokinetic profile of three different regimes of cholecalciferol supplementation in terms of 25OHD exposure and their safety profiles. Methods: We evaluated, in healthy subjects affected by vitamin D deficiency (defined as 25OHD<20 ng/mL), 18 to 60 years of age, the efficacy of three different oral supplementation regimens: daily 10, 000Iu administered for 8 weeks, weekly 50, 000Iu for 12 weeks and biweekly 100, 000Iu for 12 weeks. Serum 25OHD was dosed at baseline, at week 2, 4, 8 in all three groups and also at week 12 in the 50, 000 and 100, 000Iu groups (the blood sample was taken before the drug administration if scheduled on the same day). Baseline characteristics and 25OHD changes from baseline to the various observation points were tested with ANOVA and t-test. 25OHD was measured by the IDS-ISYSMulti-Discipline automated analyser (Immunodiagnostic System, Boldon, UK) based on chemiluminescence technology. The CV intra-assay measured in our laboratory was 6% (inter-assay CV 9%). The study was authorized by the local ethical committee (protocol DIBA/11. Supported by Abiogen Pharma, Italy). Results: A total of 75 subjects were randomized to receive one supplementation regimen. The descriptive of the sample at baseline and relative 25OHD levels at the various observation points are reported in table 1 . 25OHD increased significantly already at week 2 in all three groups (p=0.000). At week 2, 100% of the subject of the daily regimen group presented 25OHD levels >20ng/mL, 96% in the weekly and 88% in the biweekly ones. In addition, the 25OH levels of the daily regimen group at week 8 were higher than both the ones of the weekly and the biweekly regimen groups both at week 8 and week 12 (p<0.000 vs both groups). No serious adverse event occurred. Conclusion: All the three different regimens proved to be effective in correcting vitamin D deficiency already after 1 months (2 weeks for the daily regimen). A more refracted approach seems to more effective than the bolus-based regimens. The safety profile was excellent in all groups. References: [1]R. Bouillon, Comparative analysis of nutritional guidelines for vitamin D, Nat. Rev. Endocrinol. 13 (2017) 466–479. https://doi.org/10.1038/nrendo.2017.31 . Disclosure of Interests: Angelo Fassio Speakers bureau: Angelo Fassio reports personal fees from: Abiogen and Novartis, outside the submitted work., Giovanni Adami: None declared, Ombretta Viapiana: None declared, Giovanni Orsolini: None declared, Alessandro Giollo: None declared, Maurizio Rossini Speakers bureau: AbbVie, Abiogen, Amgen, BMS, Eli-Lilly, Novartis, Pfizer, Sanofi, Sandoz and UCB, Davide Gatti Speakers bureau: Davide Gatti reports personal fees from Abiogen, Amgen, Janssen-Cilag, Mundipharma, outside the submitted work.